Analisis - Elina Elina; Maimunah Maimunah; Yenita Roza (Universitas Maritim Raja Ali Haji, 2022)
The Minimum Competency Assessment (AKM) is a system used as a source of information to map and evaluate the quality of the education system that presents problems in various contexts. This study aimed to describe SMP/MTs mathematics teachers' ability to make AKM-type questions. This type of research is descriptive and qualitative with the survey method. The subjects of this study were the mathematics teachers of SMP/MTs in the Districts of Siak Kecil, Bukit Batu, and Bandar Laksamana, totaling 21 people, then the data taken were analyzed descriptively. The scoring guideline is based on the indicators for writing AKM questions contained in the scoring rubric. The results of this study indicate that the ability of teachers to make AKM-type questions is still low, namely, on context indicators, The questions made by the teacher have not used the context of numeration, both personal, scientific, and socio-cultural contexts, and on the stimulus indicators, teacher-made questions still use conventional stimuli, and there is no novelty in them. Teachers must have skills in making AKM-type questions, so training and guidance are needed.